Introduction to communication systems - Stremler, Ferrel (Reading, Massachusetts : Addision-Wesley Publishing Company, 1990)
This textbook presents an introduction to communication systems with an emphasis on signal design and modulation. The book carefully develops the mathematical principles upon which such systems are based, using examples from a wide variety of current communications systems wherever possible. These range from commercial broadcasting and telephone systems to satellite telemetry and radar.
Includes index.
Keywords: TELECOMMUNICATION